2019
DOI: 10.1128/jcm.01346-19
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Revised Version of an Immunochromatographic Assay for Detection of mecA - and mecC -Mediated Methicillin Resistance in Staphylococci

Abstract: D etection of methicillin resistance in staphylococcal isolates is crucial to quickly optimize treatment in cases of severe staphylococcal infections. Rapid genetic or phenotypic tests have been developed to detect isolates harboring the mecA gene, which is responsible for methicillin resistance related to additional penicillin-binding protein 2a (PBP2a) expression. The discovery in 2011 of a mecA variant, named mecC, encoding PBP2c and showing only 70% nucleotide sequence homology, was a real challenge for la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The improved analytical performance in detecting PBP2a of the SACCT compared to the previous version comes at the cost that it can no longer detect PBP2a in mecC -positive S. aureus isolates ( 14 , 15 ). Since the prevalence of mecC -positive S. aureus isolates is currently very low, we do not consider this a major drawback.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The improved analytical performance in detecting PBP2a of the SACCT compared to the previous version comes at the cost that it can no longer detect PBP2a in mecC -positive S. aureus isolates ( 14 , 15 ). Since the prevalence of mecC -positive S. aureus isolates is currently very low, we do not consider this a major drawback.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the SACCT displayed superior sensitivity (100%) and the same specificity (100%) in detecting PBP2a-mediated β-lactam resistance in S. aureus , as well as in CoNS isolates, compared to the old version ( 14 , 15 ). In these studies, the performance of the SACCT has been evaluated with isolates cultivated for 18 to 4 h. This implies that this assay can be employed one workday after the Gram stain identification of staphylococci in native materials at the earliest.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, no improvements were observed in the detection of the PBP2c between the current and the previous version of the PBP2a SA culture colony test (SACCT). Therefore, a negative result with the PBP2a SACCT does not imply methicillin susceptibility, since the isolate can be a mecC -positive MRSA [ 42 ].…”
Section: Phenotypic Methods For Antimicrobial Resistance Detection In S Aureusmentioning
confidence: 99%
“…For example, the blood culture-dependent three-hour short incubation protocol combines MALDI TOF identification with the qualitative immunochromatographic PBP2a detection test assay (Alere) to detect methicillin resistance, yielding a sensitivity and specificity of 87.5% and 100%, respectively [ 68 , 69 ]. Recently, a revised version of an immunochromatographic assay for detection of mecA - and mecC -positive MRSA has been described [ 70 ].…”
Section: Other Rapid Antimicrobial Susceptibility Testing (Ast) Phmentioning
confidence: 99%